Teaching Writing by Using RADAR (Replace, Add, Delete and Reorder) Strategy for the Eighth Graders of Junior High School - Indah Rahmalia; Vita Ganda Sari (EDULIA: English Education, Linguistic and Art Journal, 2022)
The purpose of this research is to find out whether teaching writing by using the RADAR (Replace, Add, Delete and Reorder) strategy is effective for students or not. The research population was class VIII students at SMPN 7 Payakumbuh consisting of five classes with the total is 105 students. There are two classes as samples, VIII-2 as the experimental class and class VIII-4 as the control class. The sample uses cluster sampling in selecting samples. The research instrument was a writing test. This instrument applies because the material is based on the curriculum or syllabus. Then, this instrument will be reliable because it will use inter-rater reliability. To analyze the post-test scores of both the experimental class and the control class, the researcher will use the T-test formula. After analyzing the data, it was found that the average value of the experimental class was higher than the average the mean score of the control class (60.13 > 53.7). t-count result is higher than t table (3.12> 2.042). This means that there is a significant influence from teaching writing using the RADAR strategy to the eighth graders of SMPN 7 Payakumbuh in the 2016/2017 Academic Year. It is recommended for English teachers to apply the RADAR Strategy in teaching writing.